Self-presentation in Online Professional Networks: Men's Higher and Women's Lower Facial Prominence in Self-created Profile Images - Sczesny, Sabine; Kaufmann, Michèle C. (Frontiers in Psychology, 2018)
Men are presented with higher facial prominence than women in the media, a phenomenon that is called face-ism. In naturalistic settings, face-ism effects could be driven by gender biases of photographers and/or by gender differences in self-presentation. The present research is the first to investigate whether women and men create this different facial prominence in images of themselves. In a controlled laboratory study, 61 participants prepared a picture of themselves from a half-body photograph, allegedly to be uploaded to their profile for an online professional network. As expected, men cropped their photos with higher facial prominence than women did. However, women and men did not differ in the self-presentational motivations, goals, strategies, and personality variables under investigation, so that the observed face-ism effect could not explained with these variables. Generally, the higher participants’ physical appearance self-esteem, the higher was their self-created facial prominence.